(untitled) (The Pretoria Student Law Review, 2021)
The purpose of this paper is to develop an understanding of the Indian perspectives concerning the regulation of competition policy by the WTO, which would in turn require understanding the country’s perspectives at various Ministerial Conferences and its experience with competition policy in the first place.